The Impact of Slow Infusion Intermittent Feeding on Gavage Feeding-Associated Cardiorespiratory Deterioration in Neonatal Intensive Care Unit Infants - Mi Jin Kim; Hyun Su Kim; Young Hwa Jung; Chang Won Choi (Korean Society of Neonatology, 2023)
Purpose Infants in the neonatal intensive care unit (NICU) often show cardiorespiratory deterioration during gavage feeding. We aimed to determine whether slow infusion intermittent feeding (SIIF) can reduce respiratory deterioration during gavage feeding in preterm infants in the NICU. Methods Data on preterm infants whose gavage feeding method was changed to SIIF (1-hour infusion with an infusion pump and 2-hour rest within a 3-hour interval) from bolus gravity feeding (2- or 3-hour interval) due to feeding-associated cardiorespiratory deterioration were retrospectively reviewed. A significant cardiorespiratory event was defined as a saturation level below 80% or heart rate below 80 bpm. We compared the frequency of cardiorespiratory events and the level of respiratory support 24 hours before and after the application of SIIF. Results A total of 34 infants were enrolled and analyzed. The total frequency of desaturation or bradycardia significantly decreased after SIIF application (8.94 vs. 5.03, P=0.001). The frequency of feeding-related bradycardia and desaturation also significantly decreased (4.15 vs. 1.68, P=0.008). Out of 34 patients, 11 (32.4%) had a decreased level of ventilator support within 1 day after SIIF. The respiratory severity scores of the 10 patients who received invasive ventilator support decreased significantly after SIIF (5.24 vs. 4.59, P=0.032). Conclusion SIIF significantly decreased gavage feeding-associated cardiorespiratory events and reduced respiratory support in approximately one-third of subjects. Therefore, SIIF may be a therapeutic option for gavage feed-associated respiratory deterioration in preterm infants in the NICU.